Z polskiej leksykografii przekładowej. Bibliografia słowników z językiem rosyjskim za lata 2005–2011 w układzie chronologicznym - Wojan, Katarzyna (Przegląd Rusycystyczny, 2013)
Katarzyna Wojan Uniwersytet Gdański, Gdańsk, Poland finkf@unigda.pl ИЗ ПОЛЬСКОЙ ПЕРЕВОДНОЙ ЛЕКСИКОГРАФИИ. БИБЛИОГРАФИЯ СЛОВАРЕЙ С РУССКИМ ЯЗЫКОМ ЗА ГГ. 2005-2011 В ХРОНОЛОГИЧЕСКОМ ПОРЯДКЕ Резюме Hacтoящaя cтaтья пpeдcтaвляeт coбoй библиoгpaфичecкий пepeчeнь 269 лeкcикoгpaфи-чecкиx paбoт c pyccким языкoм, издaнныx в Пoльшe в 2005–2011 гг. Библиoгpaфичecкий спиcoк cocтоит из двyx чacтeй: I. Лингвиcтичecкиe cлoвapи: филолoгичecкиe и тepминoлoгичecкиe, II. Энциклoпeдичecкиe cлoвapи: тeмaтичecкиe, биoгpaфичecкиe и библиoгpaфичecкиe. Maтepиaл к библиoгpaфии coбpaн и кaтaлoгизиpoвaн нa ocнoвe библиoгpaфичecкиx иcтoчникoв, нaучныx тpyдoв, пoдпиcныx кaтaлoгoв и кaтaлoгoв пoльcкиx нaучныx библиотeк. Cocтaвлeниe тaкого oбшиpнoгo библиoгpaфичecкoгo пepeчня cвидeтeльcтвyeт, нeсoмнeннo, o тoм, чтo — c тoчки зpeния издaтeлeй, pacсчитывaющиx нa зaитepecoвaннocть пoкyпaтeлeй — pyccкий язык вcё вpeмя принaдлeжит к гpyппe пpecтижныx языкoв c выcoким oбщecтвeннo-кoммyникaциoнным cтaтycoм, cyщecтвeнныx в мeжэтничecкиx и мeжкyльтypныx кoнтaктax. Hacтoящaя библиoгpaфия oтpaжaeт издaтeльcкyю динaмикy в Пoльшe и oткpытocть нa pyccкий язык. FROM POLISH TRANSLATION LEXICOGRAPHY. BIBLIOGRAPHY OF DICTIONARIES WITH RUSSIAN LANGUAGE, YEARS 2005–2011, IN CHRONOLOGICAL ORDER Summary The article contains a list of 269 lexicographical items (each including Russian language), published in Poland during the years 2005–2011. The bibliography, composed in chronolo-gical order, has been divided into two sections: I. Linguistic dictionaries: philological and terminological and II. Encyclopedic dictionaries: field, biographical and bibliographical. The material in question has been excerpted and catalogued on the basis of bibliographical sources, scientific publications, publishing and library catalogues, available at the time. The fact that so much bibliographical material has been collected proves that for publishers, Russian is still a prestigious language, which enjoys a high social and communicative status. The bibliography exemplifies editorial dynamics and welcoming attitude towards Russian language on the part of national publishers, agencies and scientific centers